v.2 (London, 2009)
Comprising the states of Bangladesh, Bhutan, India, Nepal, Pakistan, Sri Lanka, and the Maldives, South Asia has gained considerable international visibility over the past decade. Nuclear proliferation, the rapid evolution of India as a major global economic player, the emergence of new markets, cross-border terrorism, and issues of climate change and the environment are prominent among the factors that have contributed to the growing importance of the region. This has led to a commensurate growth of interest in the modern politics of South Asia, and a vast expansion of in scholarly work. This new four-volume collection from Routledge brings together the best and most influential research to make sense of this ever-expanding corpus. And while each of the four volumes has been carefully designed by the collection's editor to be self-contained, they are also helpfully linked to one another through a general introduction (which places the assembled materials in their intellectual and historical context), cross-referencing, a general index, and an annotated bibliography of further readings. Each of the five volumes is organized around the following themes: History, Political Theory and Institutions; Society, Religion, Political Culture, and Movements; Political Economy; and International Relations to provide a readily accessible and comprehensive research and pedagogic resource which will be especially welcomed by scholars, students, policy-makers, and anyone else with a serious interest in the politics of this fascinating region.
Keywords: South Asia-Politics and government